2012
DOI: 10.1038/nature10766
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine protection against acquisition of neutralization-resistant SIV challenges in rhesus monkeys

Abstract: Summary Preclinical studies of HIV-1 vaccine candidates have typically shown post-infection virologic control, but protection against acquisition of infection has previously only been reported against neutralization-sensitive virus challenges1–3. Here we demonstrate vaccine protection against acquisition of fully heterologous, neutralization-resistant virus challenges in rhesus monkeys. Adenovirus/poxvirus and adenovirus/adenovirus vector-based vaccines expressing SIVsmE543 Gag, Pol, and Env antigens resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
492
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 430 publications
(519 citation statements)
references
References 29 publications
22
492
5
Order By: Relevance
“…In agreement with those findings, we report that our SIVmac239-based vaccine elicited systemic and mucosal anti-Env humoral immune responses able to significantly delay acquisition of the heterologous SIVsmE660, and SIV-specific cellular responses that efficiently contribute to postacquisition control of viral replication. Cellular immune responses are important for limiting the levels of systemic viral replication early after infection, and this control of primary viremia can be very efficient, even when Env is not part of the vaccine (19,25,26). In addition, using CMV-based viral vectors as vaccine, it was shown that strong cellular immunity distributed in mucosal effector sites could efficiently control viral replication locally, preventing pathogenic viral dissemination and establishment of systemic infection (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with those findings, we report that our SIVmac239-based vaccine elicited systemic and mucosal anti-Env humoral immune responses able to significantly delay acquisition of the heterologous SIVsmE660, and SIV-specific cellular responses that efficiently contribute to postacquisition control of viral replication. Cellular immune responses are important for limiting the levels of systemic viral replication early after infection, and this control of primary viremia can be very efficient, even when Env is not part of the vaccine (19,25,26). In addition, using CMV-based viral vectors as vaccine, it was shown that strong cellular immunity distributed in mucosal effector sites could efficiently control viral replication locally, preventing pathogenic viral dissemination and establishment of systemic infection (27).…”
Section: Discussionmentioning
confidence: 99%
“…The RV144 clinical trial showed modest protection against infection, and this protection apparently correlated with anti-Env bAb, especially IgG antibodies against the V1V2 region (22, 23), but no evidence of vaccine-induced virus control was found in the individuals who became infected. Clearly, a vaccine regimen able to prevent acquisition (11,19,20,24) and reduce viral replication after infection has become possible (11,19,24) using the macaque model. In agreement with those findings, we report that our SIVmac239-based vaccine elicited systemic and mucosal anti-Env humoral immune responses able to significantly delay acquisition of the heterologous SIVsmE660, and SIV-specific cellular responses that efficiently contribute to postacquisition control of viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…The soluble near fulllength gp41 might be an attractive candidate for detection of gp41 Abs in HIV infected individuals. The recent RV144 trial showed a correlation between protection against HIV-1 infection and generation of Abs to the gp120 variable loop V2 (6,69). The near full-length gp41 trimers can be used in conjunction with gp120 to further improve the immunogenicity of the vaccine to induce binding and neutralizing Abs as well as cellular responses.…”
Section: Discussionmentioning
confidence: 99%
“…There has been substantial activity using HAdV-26 (Barouch et al, 2012) and chimpanzee adenovirus-based vectors (Ewer et al, 2013). Adenoviruses remain attractive for vaccine development since some of them prime innate and adaptive responses, and there have been clear advantages of maximizing and optimizing the breadth of properties within the Adenoviridae to define the most effective vectors in vaccine regimens.…”
Section: Adenovirus-based Vectors: Maximizing Opportunities and Optimmentioning
confidence: 99%